Development of tumor-specific caffeine-potentiated chemotherapy using a novel drug delivery system with Span 80 nano-vesicles - NAKATA, HIROSHI (Oncol Rep, 2015)
In recent years, chemotherapy with caffeine has manifested potently high efficacy against osteosarcoma, although adverse effects have been observed. Recently, we developed a novel drug delivery system (DDS) with nonionic vesicles prepared from Span 80 which have promising physicochemical properties as an attractive possible alternative to commonly used liposomes. Herein, we demonstrated that tumor-specific caffeine-potentiated chemotherapy for murine osteosarcoma administered by a novel DDS with Span 80 nano-vesicles showed significant antitumor effects as well as limited adverse effects. The osteosarcoma cell line, LM8, was transplanted into C3H/HeJ mice which then were administered therapeutic agents. Ifosfamide (IFO) was employed as well as caffeine as an enhancer. Span 80 vesicles containing IFO and/or caffeine were freshly prepared. On days 0, 2 and 4, different combinations of the agents were administered to mice: IFO alone (direct i.v.), IFO vesicles (IV), IV + caffeine, IV + caffeine vesicles (CV), PBS alone vesicles (PV), and PBS alone as negative control (PBS i.v.). Then, the mice were sacrificed on day 7. Antitumor effects of the reagents were also analyzed in vitro. Moreover, fertility examination was performed. In vitro, a combination of IV+CV showed significant induction of apoptosis in the early phase. Tumor volumes in the IV+CV group were significantly reduced compared with the other groups. Histological analyses showed that the IV and IV+CV groups had significantly lower viable tumor areas. The IFO direct i.v. group showed a certain grade of renal injury as well as marked suppression of spermatogenesis, while the IV or IV+CV group showed no marked changes. The fertility test revealed that the male mice with IV+CV administration had normal fertility, and no malformations were detected in their progeny. This DDS model is of potential importance for clinical application in the therapy of metastatic osteosarcoma.